Evaluation of NAFTA. - WEINTRAUB, Sidney (1997)
Revisits some of the arguments made against NAFTA at the time of its creation and subject them to a reality check three years later. Focuses on arguments made in the United States with respect to free trade with Mexico, which was the source of most of the controversy. Sets criteria that should not be used to evaluate NAFTA, and assesses the results of the agreement based on criteria that should be used.